Respon Pertumbuhan dan Hasil Beberapa Tanaman Microgreens Famili Brassica terhadap Jenis Media Tanam - Lestari, Fipih Mawar; Rahayu, Yayu Sri; Supriadi, Devie Rienzani; Rohaeni, Wage Ratna (Paspalum: Jurnal Ilmiah Pertanian, 2024)
This research aims to determine the growth of Brassica plant species under various planting media. The study was conducted in a room at Building A, Faculty of Agriculture, Campus 2, Universitas Singaperbangsa Karawang, in Margasari Village, East Karawang District, Karawang Regency, West Java. The experiment took place from April to May 2024. The research method employed a Randomized Block Design with a factorial pattern consisting of two factors. The first factor is the Brassica family (t), divided into three levels, while the second factor is the planting media (m), also divided into three levels. There were a total of nine treatments, each repeated three times, resulting in 27 experimental units. Each unit contained seven plant samples. The effects of treatments were analyzed using analysis of variance (ANOVA), and if the F-test at the 5% significance level was significant, a post hoc Duncan Multiple Range Test (DMRT) was conducted. The experimental results showed an interaction between Brassica family and planting media on growth parameters, including plant height growth rate, leaf emergence age, fresh weight, and dry weight. Cabbage plants grown in soil yielded the best results in terms of fresh weight, while purple cabbage plants grown in cocopeat media performed best in terms of dry weight. Radish plants grown in peatmoss media exhibited the best growth rate, leaf emergence age, fresh weight, and dry weight. Broccoli plants grown in soil showed the best results in terms of leaf emergence age, while broccoli plants in cocopeat media excelled in fresh weight.